Wealth and class analysis: exploitation, closure and exclusion - Waitkus, Nora; Savage, Michael; Toft, Maren (Sociology, 2024)
Wealth inequalities are increasingly prominent in contemporary societies but they have not been systematically addressed by sociological class analysis. However, class analysis should have a lot to offer: in the literature on wealth inequality, wealth is often approached as a unidimensional distribution - a quantity one can possess more or less of, crystallized in notions of the Top 1%. In this theoretical intervention, we discuss ways in which class analysis can address the gravity of wealth inequality by returning to the origins in the thinking of Marx and Weber, where capital accumulation and property organization were given central stage. Drawing on more recent contributions from Bourdieu, and integrating insights from political economy, theories of racial capitalism and feminist perspectives, we outline ways to enrich class theory through attention to housing, finance, business and debt. Our intervention allows class analysis to embrace accumulation, exploitation, closure and exclusion; making it fit for purpose to address 21st-century social changes.